Respuesta :
Answer:
A
Step-by-step explanation:
We take a look at this expression: [tex]49x^2-9[/tex] and notice that both terms are square numbers. [tex]49x^2=(7x)^2[/tex] and [tex]9=3^2[/tex].
There is a specific formula that I highly recommend you memorize involving differences of squares. It states that given the difference of squares [tex]a^2-b^2[/tex], it can always be factored into [tex](a+b)(a-b)[/tex].
Here, we can apply that. In this case, a = 7x and b = 3. So:
[tex]49x^2-9=(7x)^2-3^2=(7x+3)(7x-3)[/tex]
Thus, the answer is A.
Hope this helps!
Answer:
the answer to this is
(7x-3)(7x+3)
49x^2-21x+21x-9
49x^2-9
Step-by-step explanation: